PERTANGGUNGJAWABAN PIDANA TERHADAP PERBUATAN PIDANA YANG DILAKUKAN OLEH ANGGOTA ORGANISASI KEMASYARAKATAN BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2013 TENTANG ORGANISASI KEMASYARAKATAN - Tarulina, Hotma; Indra, Mexsasai; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesia is known as democracy, where the highest sovereignty is in the hands of the people, that is what causes free people to think and gather to create organizations. Community Organizations hereinafter referred to as mass organizations. Community Organizations are organizations established and formed by the community on a voluntary basis based on the similarity of aspirations, wills, needs, interests, activities and objectives to participate in development in order to achieve the objectives of the Unitary State of the Republic of Indonesia based on Pancasila. Community organizations basically should not conflict with Pancasila and the 1945 Constitution of the State of the Republic of Indonesia. But in reality, many deviant behaviors are performed by members of mass organizations. Lately the actions taken by members of mass organizations actually cause a variety of uneasiness and discomfort to the community by way of anarchist actions. During this time the specific arrangement of members of mass organizations who commit criminal acts in the name of mass organizations in the shade is still very minimal, making it difficult to hold accountable to the board members and members of these organization.The purpose of this thesis writing are: Firstly, to know the accountability of Criminal Officer Against Criminal Act Conducted by Members of Social Organization Based on Law Number 17 Year 2013 About Social Organization, Secondly, to know Criminal Liability Against Criminal Act Conducted by Organization Members Based Law Number 17 Year 2013 on Societal Organizations.This type of research is normative law research or can be called also research doctrinal law. From the research results of the problem there are two main points that are concluded, First, the criminal responsibility of the board of criminal acts committed. Second, criminal liability of members of community organizations committing criminal acts. Keywords: Criminal Accountability - Community Organization